Is religiosity of immigrants a bridge or a buffer in the process of integration? A comparative study of Europe and the United States - Teresa García-Mu\~noz; Shoshana Neuman (Institute for the Study of Labor (IZA), 2012)
This study reviews and evaluates the intertwined relationship between immigration and religiosity, focusing on the two sides of the Atlantic - Europe and the United States. Based on the existing literature and on a statistical analysis of several data sets (the International Social Survey Program - ISSP: Module Religion, 2008; the European Social Survey - ESS, waves 2002-2010; and the General Social Survey - GSS, waves 2002-2010) the following aspects are explored: (i) the current religious landscape of Europe and of the United States and projections for the future; (ii) religiosity of immigrants (in Europe and the United States): are they more religious than the native populations (in terms of church attendance and of prayer habits)?; (iii) how does religiosity of immigrants affect integration: is it serving as a bridge that smoothens integration into the local population, or as a buffer against the harsh integration process?; and (iv) are the intersections between religiosity and integration different in Europe and in the United States, due to historical differences in the state-religion relationship, immigration policies and concepts? The main findings are the following: (a) immigrants are indeed more religious than the populations in the receiving countries. This fact, combined with higher fertility rates and also a continued inflow of immigrants, will lead to major changes in the religious landscape, both in Europe and in the United States; and (b) while in the united States religiosity of immigrants serves as a bridge between the immigrants and the local population, in Europe it has mainly the function of a buffer and of balm to the soul.
urn:nbn:de:101:1-201206146592
Keywords: J11; J15; Z12; Z13; 330; immigration; religion; integration; Europe; United States; Migranten; Religion; Soziale Integration; Vergleich; Europa; USA